Evidence for age‐associated cognitive decline from Internet game scores. Issue 2 (3rd June 2015) - Geyer, Jason; Insel, Philip; Farzin, Faraz; Sternberg, Daniel; Hardy, Joseph L.; Scanlon, Michael; Mungas, Dan; Kramer, Joel; Mackin, R. Scott; Weiner, Michael W.
Abstract: Introduction: Lumosity's Memory Match (LMM) is an online game requiring visual working memory. Change in LMM scores may be associated with individual differences in age‐related changes in working memory. Methods: Effects of age and time on LMM learning and forgetting rates were estimated using data from 1890 game sessions for users aged 40 to 79 years. Results: There were significant effects of age on baseline LMM scores (β = −.31, standard error or SE = .02, P < .0001) and lower learning rates (β = −.0066, SE = .0008, P < .0001). A sample size of 202 subjects/arm was estimated for a 1‐year study for subjects in the lower quartile of game performance. Discussion: Online memory games have the potential to identify age‐related decline in cognition and to identify subjects at risk for cognitive decline with smaller sample sizes and lower cost than traditional recruitment methods.